Dental care in patients with periodontal disease and hearing impairment: a scoping review - Carla Mejías-Ampuero; María León-Vicencio; Patricia Melo-Mendieta; Iván Godoy-Böhm (Universidad de Concepción., 2024)
Introduction: Literature shows that individuals with disabilities, including hearing impairment, often suffer from untreated dental caries, poor oral hygiene, and compromised periodontal health, leading to adverse effects on oral health. Objetive: This study aims to analyze current evidence concerning dental care strategies for controlling, managing, and preventing biofilm accumulation in patients with hearing impairment. Materials and Methods: A systematic search was conducted in the databases Scopus, Web of Science, SciELO and PubMed between April and May 2022 to identify articles establishing a relationship between periodontal disease and hearing disability. Full-text articles published in English or Spanish between 2012 and 2022 were included. Results: Seventeen articles met the inclusion criteria and were analyzed. These included cross-sectional studies, cohort studies, clinical trials, case reports, and case-control studies. Most studies reported fair to poor oral health status among individuals. Nine different interventions or management approaches for treating periodontal disease in patients with hearing impairment were identified. Conclusions: The current global evidence on the association between periodontal disease and hearing impairment is very limited. Dentists may need to employ various strategies to address communication barriers, as outlined in this study.